Legal Recommendations on the Establishment of Worker Representative Organization in Enterprise in Accordance with International Standards - Le Thu, Nguyen (VNU Journal of Science: Legal Studies; Vol 37 No 4DO - 10.25073/2588-1167/vnuls.4391, 2021)
In addition to Trade Union, from 1 st January 2021, employees in Vietnam are entitled to establish and join worker representative organizations in enterprises. This is one of the new legislative developments that lack clarifying regulations . In this context, the International Labor Organization (ILO) published a Digest of decisions and principles of the Freedom of Association Committee of the Governing Body of the ILO, based on about 200 cases presented to this organization. Therefore, the research on this vital document might provide Vietnam with the opinions of international experts and practical experiences from many countries worldwide on the concerned issue for further developing regulations on freedom of association. As this is a big topic, this article only focuses on international standards on establishing worker representative organization, then comparing them with Vietnamese regulations to find out the gaps to be supplemented.